Fauna associated with cold seeps in the deep Colombian Caribbean. (July 2021) - Dueñas, Luisa F.; Puentes, Vladimir; León, Jorge; Herrera, Santiago
Abstract: Cold-seep chemosynthetic communities are found in patchy areas where methane and other hydrocarbons leak through the seafloor. Although relatively common in continental margins, chemosynthetic communities in the Caribbean region are poorly known. Their existence in Colombian waters has been suggested by the presence of carbonates and specimens of seep- specialist families obtained through trawling surveys, and seismic and multi-beam data. Habitat models incorporating bathymetry and backscatter data have also predicted the presence of hard ground areas (presumed authigenic carbonates formed due to chemosynthetic activity), which are consistent with water column plume anomalies. Here, we present the first characterization of the megafauna found in cold-seep communities in the Colombian Caribbean between 2300 and 3300 m using seafloor images taken with a towed camera system and samples collected through piston coring. Chemosynthetic communities at these sites resemble those found off Trinidad and Tobago and the Gulf of Mexico. Dominant species include tubeworms ( Lamellabranchia sp. and Escarpia sp.), mussels ( Bathymodiolus sp.), shrimp ( Alvinocaris sp.), and squat lobsters ( Munidopsis sp.). These results represent foundational knowledge of deep-sea ecosystems in the southern Caribbean. Highlights: Include 3 to 5 bullet points (maximum 85 characters, including spaces, per bullet point). First characterization of cold-seep communities in the Colombian Caribbean. Image and piston core assessment at 2300–3300 m deep. Dominant species include tubeworms, mussels, shrimp, and squat lobsters.